Towards machine-assisted meta-studies: the Hubble constant. Issue 3 (23rd December 2019) - Crossland, Tom; Stenetorp, Pontus; Riedel, Sebastian; Kawata, Daisuke; Kitching, Thomas D; Croft, Rupert A C
ABSTRACT: We present an approach for automatic extraction of measured values from the astrophysical literature, using the Hubble constant for our pilot study. Our rules-based model – a classical technique in natural language processing – has successfully extracted 298 measurements of the Hubble constant, with uncertainties, from the 208 541 available arXiv astrophysics papers. We have also created an artificial neural network classifier to identify papers in arXiv which report novel measurements. From the analysis of our results we find that reporting measurements with uncertainties and the correct units is critical information when distinguishing novel measurements in free text. Our results correctly highlight the current tension for measurements of the Hubble constant and recover the 3.5σ discrepancy – demonstrating that the tool presented in this paper is useful for meta-studies of astrophysical measurements from a large number of publications.